CORRECTION BY THE PREPARATION OF PLANT POLYPHENOLS OF METABOLIC CHANGES OF TISSUES OF RATS ORAL CAVITY UNDER CONDITIONS OF INTRAUTERINE HYPOXIA AND CARIOGENIC DIET - Ivanov, V.S.; Tkachenko, Ye.K.; Dienha, O.V.; Schnayder, S.A.; Pyndus, T.O. (World of Medicine and Biology, 2021)
The work is devoted to the study of the effect of the preparation of plant polyphenols on the dental status and the state of the tissues of the oral cavity of rats under conditions of intrauterine hypoxia and cariogenic diet. The experiment was carried out on 36 white rats of both sexes: 30 females and 6 males. A preparation of plant polyphenols had a caries-preventive and parodontoprotective effect in the offspring of rats under conditions of intrauterine hypoxia and a cariogenic diet. In the oral mucosa, the preparation showed anti-inflammatory and antioxidant effects. The preparation improved state of collagen in the intercellular matrix of the connective tissue of rat parodontal tissue as a result of normalization of the levels of general and free oxyproline in the oral mucosa, as well as general oxyproline in the alveolar bone of rats.
Keywords: hypoxia; caries-prophylactic effect; metabolic markers; plant polyphenols; rats